Pengelolaan Sumberdaya Pesisir Yang Berkelanjutan Bagi Pengembangan Kawasan Pesisir Di Kecamaan Galesong Selatan Kabupaten Takalar - Aulia, Diza; Jufriadi, Jufriadi; Budiharto, Tri (Journal of Urban Planning Studies, 2024)
Sustainable Management of Coastal Resources for the Development of Coastal Areas in South Galesong District, Takalar Regency" This study aims to determine the potential that exists in the coastal area of South Galesong District in the development of coastal areas and strategies in developing coastal areas of South Galesong District, Takalar Regency. The population in the coastal area is the target of this study. The data collection approach is observational, it is decided that sustainable resource management. Another potential resource that can be developed is tourism development. From this potential, it is necessary to develop coastal areas with sustainable management of coastal resources. The results showed that the coastal area in South Galesong District with the highest level of development of coastal resource potential was in Bontorannu Village, where there was potential for the development of tourism and other types of fish, as well as Mangindara and Bonto Kanang villages which had a moderate level of development and potential for milkfish development. shrimp, coral reefs, seagrass beds, and mangroves. To maximize utilization, management, techniques for catching and processing fishery products, as well as a marketing system as a center for economic development for fishing communities in Takalar Regency, develop an integrated fishery area around the coastal area of South Galesong District. Development of better facilities and infrastructure for the operationalization of the coastal area of South Galesong District.